Spatial Interactions and the Commercialisation of Academic Patents: The Chinese Experience - Jiafeng Gu (Science, Technology & Society, 2022)
Studies on academic patent commercialisation are well documented. However, spatial effects are seldom considered, which could lead to potentially misleading analytical results. This study addresses this concern by applying the spatial analysis method to investigate how university-level factors and commercialising academic patents are related. Using a comprehensive dataset of university patents from 1815 Chinese universities in 2016, we find that public research funding of universities, industrial research funding, the number of scientific research personnel, the number of monographs published, and the number of awarded achievements are positively related to the commercialisation of academic patents. However, the number of teaching and research personnel and the number of academic papers published are negatively related. There are positive spatial spillover effects in commercialising academic patents among neighbouring universities, but there will be negative spatial spillover effects in funding competition.